Cybercrime: A Potential Threat to Global Community - Mohajan, Haradhan Kumar (Studies in Social Science & Humanities, 2025)
Cybercrime is a criminal activity that takes place through the use of computer and internet as instruments for illegal operations. It is a common phenomenon that can take many shapes, and can occur anytime and anyplace through the use of a number of methods, depending on the skill-set and goal of the criminals. It covers a wide variety of criminal activities, such as computer related offences, integrity and availability of computer data, and acts against the confidentiality, content and copyright related offences that create stress on the society in the form of economical disrupt, psychological disorder, threat to national defense, etc. Most of the cybercrimes are done on different parts of the world, and money is the major motivator for many cyber criminals, and still beyond the reach of the law. The cybercrime is a major threat to cyber security and computer data system in the era of globalization due to the rapid spread of information and communication technology (ICT).